Patient safety culture: factors that influence clinician involvement in patient safety behaviours. Issue 6 (19th August 2010) - Wakefield, John G; McLaws, Mary-Louise; Whitby, Michael; Patton, Leanne
Abstract : Objectives: To develop an understanding of the factors that influence patient safety-related behaviours by nurses, doctors and allied health staff employed by Queensland Health, using a theory-driven behavioural model. Design: Cross-sectional survey analysed with multiple logistic regression. Setting: Metropolitan, regional and rural public hospitals in Queensland, Australia. Participants: 5294 clinical and managerial staff. Main outcome measures: The Theory of Planned Behaviour was used to develop behavioural models for high-level Patient Safety Behavioural Intent (PSBI) of senior and junior doctors, senior and junior nurses, and allied health professionals. Multiple logistic regression analysis was used to identify factors that significantly influenced PSBI between the five professional groups. Results: The factors that influence high-level PSBI give rise to unique predictive models for each professional group. Two factors stand out as influencing high-level PSBI for all healthcare workers (HCWs): (1) Preventive Action Beliefs (adjusted OR 2.38), HCWs' belief that engaging in the target behaviours will lead to improved patient safety; and (2) Professional Peer Behaviour (adjusted OR 1.79), perceptions about the patient safety-related behaviours of one's professional colleagues. Conclusions: Professional peer-modelling behaviours and individuals' beliefs about the value of those behaviours in improving patient safety are important predictors of HCWs' patient safety behaviour. These findings may help explain the limitations of current knowledge-based educational approaches to patient safety reform. Use of the behavioural models developed in this study when designing future patient safety improvement initiatives may prove more effective in driving the behavioural change necessary for improved patient safety.